Optimalisasi Peran OSIS sebagai Strategi Peningkatan Prestasi dan Pengembangan Program di Sekolah Menengah Atas - Maryanah, Rina; Syafe'i, Ahmad; Permana, Galih (Epistemic: Jurnal Ilmiah Pendidikan, 2022)
This study highlights the importance of the Student Council (OSIS) in supporting school activities and developing relevant programs to enhance student achievement at SMA Islam Progresif Daarussalaam. It aims to illustrate how optimizing OSIS's role can improve academic performance and develop school programs. The qualitative research employs a case study approach involving in-depth interviews with OSIS members, teachers, and school staff, and thematic data analysis. The research design includes data collection from various OSIS activities, such as routine programs, Islamic and National holiday commemorations, and both external and internal events. Key findings indicate that OSIS significantly bridges students with school administration, facilitating effective communication, and developing programs that meet student needs, thereby enhancing academic performance and fostering leadership skills, responsibility, and discipline. The findings underscore the importance of good coordination between OSIS and school administration for program success, reinforcing student engagement theory and highlighting the importance of institutional support. This research contributes to the literature and knowledge in educational management and student organization development, providing insights into how active student involvement and institutional support can enhance student achievement and character development.